Implementasi Teori Belajar Behavioristik dalam Pembelajaran Matematika - Prima Mytra; Andi Asrafiani; Ahmad Budi; Hardiana Hardiana; Irmayanti Irmayanti (IAI Muhammadiyah Sinjai, 2022)
The purpose of this study is to describe the advantages and disadvantages and implementation of Behavioristic learning theory in mathematics learning. The research method used is literature research and conducting studies with Behavioristic learning theorists and using secondary data. The results of the study are as follows: (1) behavioristic learning theory is good for students who are still children or at the elementary and some junior high school levels, (2) this theory is good for use in lessons that require speed, spontaneity, flexibility, etc., (3) simple and easy to apply because they do not pay much attention to elements.